Effect of Tuber Sections, Heat Treatment and Rehydration with Process Chemicals on the Physicochemical Properties of Sweet Potato (Ipomoea Batatas L. (Lam)) Flour - M. C, Iheagwara; I. H, Chibuzo; J. C, Ibeabuchi (Journal of Food Technology Research, 2019)
The impact of tuber sections and some processing conditions on the physicochemical properties of sweet potato (Ipomoea batatas L. (Lam)) flour was investigated. Flour samples were generated as fresh, boiled and steamed from the head, middle, tail and the whole tuber. All the samples were subjected to some physicochemical analyses such as swelling index (SI), water absorption capacity (WAC), oil absorption capacity (OAC), total soluble solids (TSS), blue value index (BVI), gelling point temperature (GPT), boiling point temperature (BPT) and pH in order to assess the effect of tuber section, heat treatment and post-milling rehydration properties of flour in different steeping solution of varying concentrations. The result showed that the proximate composition of the flour from the tuber sections and the whole did not differ significantly (p < 0.05). The influence of steeping solution type (SST) was not significant (p > 0.05) on WAC, SI (boiled and steamed) and TSS (raw) while steeping solution concentration (SSC) effected significant variations (p < 0.05) in all the tested parameters of the flour. Also, the parameter analytical temperature (PAT) caused significant differences (p < 0.05) in all the test parameters.